Properties of R Plasmids Determining Gentamicin Resistance by Acetylation in Pseudomonas aeruginosa - Jacoby, George A. (1974)
Two clinical isolates of Pseudomonas aeruginosa, one a pyocin type 5 strain from Atlanta, could transfer gentamicin resistance by conjugation. Donor and recipient strains inactivated gentamicin by acetylation. The R plasmids, pMG1 and pMG2, also determined resistance to sisomicin, another substrate of gentamicin acetyltransferase I, sulfonamides, and streptomycin, but not resistance to kanamycin, neomycin, tobramycin, butirosin, or BB-K 8. They were transmissible to many strains of P. aeruginosa, including a Rec(−) strain, but not to Escherichia coli or other enterobacteriaceae. These R plasmids were compatible with R plasmids transmissible to P. aeruginosa from E. coli, including members of C, N, P, and W incompatibility groups. From a strain carrying pMG1 and a compatible plasmid, pMG1 was transferred independently but transfer of the second plasmid often resulted in cotransfer of pMG1. In contrast, pMG1 and pMG2 were incompatible with pseudomonas R plasmids R931 and R3108, and with R931 they readily formed recombinant plasmids. The four plasmids in this incompatibility group determine additional biological properties, including resistance to inorganic and organic mercury compounds, to ultraviolet light, and to certain deoxyribonucleic acid phages. pMG1 and pMG2 also phenotypically inhibited pyocin production. Consequently such R plasmids alter the phage and pyocin types of their host strains.